The FRAX-based Lebanese osteoporosis treatment guidelines: rationale for a hybrid model. Issue 1 (January 2017) - Chakhtoura, M.; Leslie, W.; McClung, M.; Cheung, A.; Fuleihan, G.
Abstract Summary We describe our approach to develop FRAX-based osteoporosis treatment guidelines in Lebanon, a country with low-moderate fracture rates. A hybrid assessment algorithm that combines a fixed 10 % intervention threshold until age 70 years, and an age-dependent threshold thereafter, was deemed most suitable. Introduction The FRAX risk calculator is used to guide intervention thresholds in several national osteoporosis guidelines. This study aimed to describe the approach in developing FRAX-based osteoporosis treatment guidelines in Lebanon, a country with relatively low fracture rates. Methods We reassessed previous national guidelines combined with an evaluation of age-dependent and fixed FRAX-based intervention threshold models used in the UK, the USA, and Canada. We took into consideration the risk for major osteoporotic fractures (MOF) and the proportions of subjects considered for therapy using such thresholds, before finalizing a model for Lebanon. Results The new Lebanese guidelines retained the recommendation to treat individuals with fragility fracture at the hip or spine. A femoral neck T-score ≤−2.5 in subjects without fractures was dropped, since it would imply consideration of therapy for individuals with a 10-year risk for MOF of <10 %, up to age 75 years in women. After considering the impact of both age-dependent and fixed intervention thresholds, we chose a new hybrid algorithm, combining a fixed 10 % treatment threshold until age 70 years and an age-dependent threshold thereafter. Conclusion The Lebanese FRAX-based hybrid model takes into consideration the risk for MOF and the proportions of subjects considered for treatment. This model avoids consideration of drug therapy in a large proportion of younger subjects at low risk for fracture and targets high risk elderly individuals. It was deemed most suitable for Lebanon and may be an option for other countries with relatively low fracture rates.